The Hybridization of the Japanese Production System in the United States and East Asia (Malaysian Management Journal, 1997)
This paper examines the international transferability of the Japanese production system to the United States (US), Korea, Taiwan, Malaysia, Thailand, and Singapore, by utilizing the "application-adaptation analytical framework". Three major factors determine particular application-adaptation hybridization characteristics in individual countries: strategic necessity of industry and company; specific attributes of the elements comprising the Japanese production system; the historical, social, and managerial environment of the host countries.